The road to enchantment - McLaren, Kaya (St. Martin's Griffin, 2017)
"As a young girl, Willow's mother left their home in Washington State in a literal blaze of glory: she set the mattress of her cheating husband on fire in her driveway, roasting marshmallow peeps and hot dogs before the fire department arrived. And with that, she and her daughter set off to New Mexico, to a new life, to a world of arroyos and canyons bordering an Apache reservation. Willow was devastated. Her eccentric mother believed in this new life and set about starting a winery and goat ranch. But for Willow, it meant initially being bullied and feeling like an outsider. Today, as a grown woman, Willow much prefers Los Angeles and her job as a studio musician. But things tend to happen in threes: her mother dies, her boyfriend dumps her, and Willow discovers she is pregnant. The DeVine Winery and Goat Ranch is all she has left, even it is in financial straits and unmanageable back taxes. There is something, though, about the call of "home." She's surprised to find that her Apache best friend Darrel along with the rest of the community seems to think she belongs far more than she ever thought she did. Can Willow redefine what home means for her, and can she make a go of the legacy her mother left behind? Told with Kaya McLaren's humor and heart, The Road to Enchantment is a story about discovering that the last thing you want is sometimes the one thing you need"--